Storyline Units: An Instructional Model to Support Coherence from the Students' Perspective. Issue 7 (3rd October 2021) - Reiser, Brian J.; Novak, Michael; McGill, Tara A. W.; Penuel, William R.
ABSTRACT: The vision of the Framework and NGSS requires important shifts in teaching approaches and instructional materials. We argue that this commitment to engaging learners in meaningful practice and supporting students' epistemic agency entails that we support coherence from the students' perspective . This coherence arises when students see their science work as making progress on questions and problems their classroom community has committed to address, rather than simply following directions from textbooks or teachers. We present an instructional model, storylines, to support this form of coherence. The storylines approach includes design principles for engaging students with phenomena and problems to elicit their own questions that teachers, with support of curriculum materials, use to guide the trajectory of their sensemaking. We describe how storylines organize cycles of engaging with phenomena, questions, and sensemaking to incrementally build, test, and revise explanatory models and design solutions. Storylines are supported by a collection of instructional routines and norms that provide strategies and tools to guide teachers' work with students around phenomena, questions, and sensemaking. The routines reflect strategies for eliciting questions from anchoring phenomena, navigation to engage students as partners in managing the direction of investigations, problematizing to help students find gaps in their work so far, and putting pieces together to support students in assembling what they have figured out. We present examples from elementary, middle, and high school storyline-based units awarded the NGSS design badge to illustrate the application of these design principles in the design and enactment of storyline-based units.